1997
DOI: 10.1093/clinchem/43.10.1944
|View full text |Cite
|
Sign up to set email alerts
|

Candidate reference methods for hemoglobin A1c based on peptide mapping

Abstract: A reference method that specifically measures hemoglobin (Hb) A1c is an essential part of the reference system for the international standardization of Hb A1c/glycohemoglobin. We have developed a new method for quantification, based on the specific N-terminal residue of the hemoglobin β-chains. Enzymatic cleavage of the intact hemoglobin molecule with endoproteinase Glu-C has been optimized to obtain the β-N-terminal hexapeptides of Hb A1c and Hb A0. These peptides have been separated by reversed-phase HPLC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(45 citation statements)
references
References 18 publications
3
42
0
Order By: Relevance
“…(S Eckerbom, personal communication). Results obtained using this method closely agree with those from a proposed world standard method [20], giving about 1.2% U lower values than the Bio-Rex method in use during the Diabetes Control and Complications Trial [21].…”
Section: Glycated Haemoglobinsupporting
confidence: 75%
“…(S Eckerbom, personal communication). Results obtained using this method closely agree with those from a proposed world standard method [20], giving about 1.2% U lower values than the Bio-Rex method in use during the Diabetes Control and Complications Trial [21].…”
Section: Glycated Haemoglobinsupporting
confidence: 75%
“…31,33 The International Federation of Clinical Chemistry (IFCC) has developed a reference method that precisely measures glycated HbA1c only. 92,93 The reference measurement procedure has been defined as bN1deoxyfructosyl-hemoglobin, and the recommended SI measurement units are mmol/mol. 94 The IFCC, American Diabetes Association, European Association for the Study of Diabetes, and the International Diabetes Federation have issued a consensus statement regarding this standardization process.…”
Section: Intermittently Scanned Cgmmentioning
confidence: 99%
“…cleavage of the intact glycated hemoglobin molecule with the endoproteinase Glu-C, using HPLC-ESI/MS or HPLC-CE ( [3,4], Fig. 1(left)).…”
Section: Hplc Analysis Of Proteolysis Of Fru-hexapeptide and Deglycatmentioning
confidence: 99%
“…At each substrate concentration, the absorbance for Fru-hexapeptide was 80% of that for Fru-ValHis, indicating that about 80% of Fru-hexapeptide was digested by the protease releasing Fru-ValHis. These results indicated that FPOX is applicable for determining the amount of Fru-hexapeptide that is supposed to be liberated from HbA 1C by Glu-C endoproteinase [3,4].…”
Section: Enzymatic Measurement Of Glycated Hexapeptidementioning
confidence: 99%
See 1 more Smart Citation